End stage renal disease among ceramic workers exposed to silica. Issue 8 (1st August 1999) - Rapiti, E; Sperati, A; Miceli, M; Forastiere, F; Di Lallo, D; Cavariani, F; Goldsmith, D F; Perucci, C A
Abstract : OBJECTIVES: To evaluate whether ceramic workers exposed to silica experience an excess of end stage renal disease. METHODS: On the basis of a health surveillance programme, a cohort of 2980 male ceramic workers has been enrolled during the period 1974-91 in Civitacastellana, Lazio, Italy. For each worker, employment history, smoking data, and x ray film readings were available. The vital status was ascertained for all cohort members. All 2820 people still alive and resident in the Lazio region as in June 1994 were searched for a match in the regional end stage renal diseases registry, which records (since June, 1994) all patients undergoing dialysis treatment in public and private facilities of the region. Expected numbers of prevalent cases from the cohort were computed by applying the rate of patients on dialysis treatment by the age distribution of the cohort. RESULTS: A total of six cases was detected when 1.87 were expected (observed/expected (O/E) = 3.21; 95% confidence interval (95% CI) 1.17 to 6.98). The excess risk was present among non-smokers (O = 2; O/E = 4.34) and smokers (O = 4; O/E = 2.83), as well as among workers without silicosis (O = 4; O/E = 2.78) and workers with silicosis (O = 2; O/E = 4.54). The risk was higher among subjects with < 20 years since first employment (O = 4; O/E = 4.65) than among those employed > 20 years. CONCLUSION: These results provide further evidence that exposure to silica dust among ceramic workers is associated with nephrotoxic effects.